Pengaruh Profitabilitas, Pertumbuhan Perusahaan, Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Otomotif Yang Terdaftar Di BEI Periode 2017-2019 - Sumiyati Sumiyati; Budi Wahono; Nur Hidayah (UNIVERSITAS ISLAM MALANG, 2021)
AbstractThis study aims to determinte he effect of profitability proxied by Return on Equity (ROE), company growth, and capital structure proxied by Debt to Equity Ratio (DER) on Firm Value proxied by Price Book Value (PBV) in Registered Automotive Companies. on the Indonesia Stock Exchange for the 2017-2019 Period. The population in this study amounted to 15 automotive companies listed on the Indonesia Stock Exchange. The technique used in this study is purposive sampling with criteria, obtained a total sample of 12 companies. The analysis technique used in this research is Multiple Linear Regression, Classical Assumption Test and F test to calculate simultaneously, t test to calculate partially and the coefficient of determination to measure changes in the independent variable to the dependent variable. The results of this study indicate that the profitability proxied by Return on Equity (ROE) has a positive and significant effect on firm value, company growth has a positive and significant effect on firm value, and capital structure proxied by the Debt to Equity Ratio (DER). ) has a negative and insignificant effect, while simultaneously ROE, Growth and DER have a positive and significant influence on firm value as proxied by PBV. Keywords: Profitability, Company Growth, Capital Structure, Firm Value